2017
DOI: 10.7150/ijms.18392
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA AFAP1-AS Functions as a Competing Endogenous RNA to Regulate RAP1B Expression by sponging miR-181a in the HSCR

Abstract: Background: Long noncoding RNAs (lncRNAs) have recently emerged as important regulators in a broad spectrum of cellular processes including development and disease. Despite the known engagement of the AFAP1-AS in several human diseases, its biological function in Hirschsprung disease (HSCR) remains elusive.Methods: We used qRT-PCR to detect the relative expression of AFAP1-AS in 64 HSCR bowel tissues and matched normal intestinal tissues. The effects of AFAP1-AS on cell proliferation, migration, cell cycle, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Using TNM I stage lung adenocarcinoma samples in the TCGA database, Tian et al ( 40 ) demonstrated that FENDRR and LINC00312 had diagnostic value in patients with LUAD. A recent study has demonstrated that lncRNA can act as a ceRNA that adsorbs onto miRNAs to regulate mRNA expression ( 41 ). The ceRNA hypothesis is a novel regulatory mechanism that serves a role through miRNA competition ( 10 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using TNM I stage lung adenocarcinoma samples in the TCGA database, Tian et al ( 40 ) demonstrated that FENDRR and LINC00312 had diagnostic value in patients with LUAD. A recent study has demonstrated that lncRNA can act as a ceRNA that adsorbs onto miRNAs to regulate mRNA expression ( 41 ). The ceRNA hypothesis is a novel regulatory mechanism that serves a role through miRNA competition ( 10 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence suggests a relationship between lncRNAs and HSCR, all based on the comparative expression assays of specific lncRNAs in bowel tissue from HSCR patients and controls [73][74][75][76][77][78]. In our study we have performed a differential qRT-PCR assay in the EPCs from HSCR patients and controls, which has allowed us to identify new lncRNAs as potential regulatory elements implicated in ENS development and HSCR onset.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the limitation of the enteric nervous system (ENS) cell model of HSCR, according to previous reporting papers, two most felicitous cell lines, human SKN-SH and SH-SY5Y cells, are neuroblastoma cell lines which derived from NCCs and used to investigate the mechanism of HSCR in many articles. 2325 These two cell lines were obtained from Dr. Qiangsong Tong, at Department of Pediatric Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, China. 26 These two cell lines were used via in vitro experiments and cultivated in a humidified atmosphere of 5% CO 2 , at 37 °C, with DMEM containing high glucose levels (Boster, Wuhan, China), 10% fetal bovine serum (FBS) (Sciencell, Beijing, China), streptomycin (100 μg/mL) and penicillin (100 U/mL) (Sigma-Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%